Reluctant Accomplice : A Wehrmacht Soldier's Letters from the Eastern Front - Jarausch, Konrad, 1900-1942 (Book collections on Project MUSE., 2011)
Reluctant Accomplice is a volume of the wartime letters of Dr. Konrad Jarausch, a German high-school teacher of religion and history who served in a reserve battalion of Hitler's army in Poland and Russia, where he died of typhoid in 1942. He wrote most of these letters to his wife, Elisabeth. His son, acclaimed German historian Konrad H. Jarausch, brings them together here to tell the gripping story of a patriotic soldier of the Third Reich who, through witnessing its atrocities in the East, begins to doubt the war's moral legitimacy. These letters grow increasingly critical, and their vivid.